Numerical modeling study of the effect of softcover on the caving behavior of strata and support requirement in depillaring working - Sahoo, Sandeep Kumar (IIT(BHU) Varanasi, 2021)
Abstract is available in content.
Keywords: Numerical modeling study of the effect; softcover on the caving behavior of strata; support requirement in depillaring working